2017
DOI: 10.1556/066.2017.46.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salt level, starter culture, fermentable carbohydrates, and temperature on the behaviour of L. monocytogenes in sliced chouriço during storage

Abstract: Sliced ready-to-eat traditional meat products presented in individual packaging with more convenience to the consumer is the way that food industry tries to adapt to the new consumer tendencies.The current work assessed the survival of Listeria monocytogenes in a contaminated sliced vacuum packed chouriço with different sugar concentrations, two salt levels, and presence/absence of Lactobacillus sakei as starter culture along the storage period at two temperatures (8 ºC and 22 ºC). Neither the inoculation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Several authors have reported the use of LAB starter cultures for the production of fermented sausages [34][35][36][37][38]. For example, Wang and coworkers reported the inoculation with L. sakei as beneficial for microbiological quality against the growth of foodborne pathogens, also improving sensory characteristics [34].…”
Section: Bacteria: Lab and Gcc+mentioning
confidence: 99%
“…Several authors have reported the use of LAB starter cultures for the production of fermented sausages [34][35][36][37][38]. For example, Wang and coworkers reported the inoculation with L. sakei as beneficial for microbiological quality against the growth of foodborne pathogens, also improving sensory characteristics [34].…”
Section: Bacteria: Lab and Gcc+mentioning
confidence: 99%
“…In the tradition of meat product manufacturing, several products are seasoned with generous amounts of red wine, sometimes as high as 10% (v/w), which is added in the batter used for chouriço-a filled sausage with a natural casing that is tied in a horseshoe shape and cold smoked and dried. Wine can also be used in a marinade for whole piece products, such as cured pork loins [6,7]. In these meat products, wine has an indubitable sensory effect on their color and aroma and probably exerts an antimicrobial effect due to the presence of organic acids, ethanol, and phenolic compounds [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the low levels of ENT and E. coli observed in our samples suggest an adequate hygiene of processing/handling. Since the slicing process is recognized as a risk procedure regarding foodborne contamination, the consumption of sliced meat products at the end of the shelf life, even with the absence of foodborne pathogens in studied samples, may be appropriately evaluated [43].…”
Section: Discussionmentioning
confidence: 99%